Field notes contributed by Paul Martsching for Story County, fall 1984 - Martsching, Paulet al (1984)
Field were notes contributed by Paul Martsching for Story County, fall 1984. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed